Corrosion behavior of HVOF sprayed WC-10Co4Cr coatings in the simulated seawater drilling fluid under the high pressure. (January 2020) - Zhou, Yong-kuan; Liu, Xiao-bin; Kang, Jia-jie; Yue, Wen; Qin, Wen-bo; Ma, Guo-zheng; Fu, Zhi-qiang; Zhu, Li-na; She, Ding-shun; Wang, Hai-dou; Liang, Jian; Weng, Wei; et al.
Highlights: WC-10Co4Cr coatings with bimodal structures have superior properties than conventional structures. WC-10Co4Cr coatings have a better corrosion resistance than substrate. The bimodal coatings have better corrosion resistance than conventional coatings. The micro-galvanic corrosion is the primary corrosion mechanism of the coatings, and the crevice corrosion also exists. Abstract: Two kinds of WC-10Co4Cr composite coatings with conventional (micron-sized WC particles) and bimodal (a mixture of nano-sized and micron-sized WC particles) structures were successfully prepared on 35CrMo steel (ANSI/ASTM 4135) substrate by high velocity oxygen fuel (HVOF) technology. Scanning electron microscope (SEM) equipped with the energy dispersive spectroscopy (EDS), mechanical testing machine, microhardness tester were used to analyze the characteristics of the coatings. The coatings were immersed in the simulated seawater drilling fluid under the high pressure to simulate the deep-sea environment, and then electrochemical impedance spectroscopy (EIS), potentiodynamic polarization were carried out to investigate the electrochemical properties of the coatings and substrate. The results show the WC-10Co4Cr coating has excellent corrosion resistance and can effectively protect the substrate under the high pressure. Besides, compared with the conventional coating (CC), the bimodal coating (BC) has a denser microstructure, superior mechanical properties, lower porosity, and better corrosion resistance. The corrosion mechanism of the coatings in the simulated seawater drilling fluid under high the pressure is as follows: The micro-galvanic corrosion between the WC phase and the CoCr binder phase is the primary corrosion mechanism. Besides, the electrolyte under the high pressure is more penetrable, so the crevice corrosion also exists.